Perbandingan jumlah total bakteri, kadar lemak, dan protein susu segar pada penyimpanan suhu rendah (4 – 6° C) dan suhu ruang - Fajar Firdaus Afandi; Raden Febrianto Christi; Wendry Setiyadi Putranto (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2023)
The method and duration of storage are crucial factors determining quality of fresh milk, as assessed by total bacterial, fat content, and protein content of fresh milk. This research aims to determine the comparison of the total bacterial count, fat content, and protein content of fresh milk stored at a low temperature and at room temperature. The research subjects used were fresh milk obtained from a single cow in a single milking process, stored at a low temperature of 4 – 6 ℃ and at room temperature, and then tested and compared for the total bacterial count, fat content, and protein content after storage for the 2nd, 4th, and 6th hours. The data obtained was statistically analyzed using the student’s t-test at a confidence level of α = 95%. The result showed that there a significant difference (p<0,05) in total bacterial and fat content. Within 6 hours, at a low temperature, total bacterial increased from the initial 3,07 × 105 cfu/ml to 5,95 × 105 cfu/ml, while at room temperature, it rose to 21.02 × 105 cfu/ml. The initial fat content was 4,14%, and after 6 hours of storage, at a low temperature, fat content decreased to 3,35%, whereas at room temperature, it dropped below the SNI standard of 3 to 2,91%. As for the protein content of the milk, both at low and room temperatures, the protein did not decrease and did not show a significant difference (p<0,05). It can be concluded that up to two hours of storage, the quality of milk is not affected by temperature. However, after being stored for more than two hours, the storage temperature does impact the total bacterial count and the fat content of the milk.